ANALISIS KELAYAKAN INVESTASI PADA KEGIATAN BATUBARA KUD SINAMAR SAKATO DENGAN METODA NPV - Fendri Amir; Tri Gamela Saldy (Sekolah Tinggi Teknologi Industri Padang, 2022)
KUD Sinamar Sakato is one of the companies engaged in coal mining using an open pit system. The company has total reserves of 8,431,610 million tonnes. Mining at this company began in January 2021 with a production target of 400,000 tons of coal per year, but only reached 200,000 tons of coal in December 2021. KUD Sinamar Sakato realizes that mining companies require a lot of money, so an investment feasibility analysis is needed to determine whether the mine is economically feasible. , technical and environmental. The method used in this study is to use the Net Present Value. The NPV value in this study is greater than 0 or Rp. 496,473,602,258.14, which means that the project investment is considered feasible or profitable. The PBP value required by the company for return on investment is 2.13 years. The results of this investment feasibility analysis are profitable so that they can become a reference for the company to continue the project.